Gamma radiation dose-response of gram-positive and gram-negative bacteria - Jan, Nie Hing; Bor, Chyan Jong; Woan, Pauline Ying Liew; Rashid Elly Ellyna; Shamsudin Shuhaimi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bacterial mutagenesis induced through gamma irradiation is one of the techniques for strain improvement. The DNA changes caused by radiation and reactive oxygen species created from water radiolysis induced bacterial mutagenesis. There is always a constant demand for better quality strains from the bioprocessing industries to speed up production and increase yield. Bacillus strains are Gram-positive bacteria whereas Escherichia coli is a Gram-negative bacteria; they are all model organisms used by the bioprocessing industries. This study investigates the effect of acute gamma irradiation on Gram-positive Bacillus megaterium NMBCC50018, Bacillus subtilis NMBCC50025 and Gram-negative Escherichia coli. Samples were irradiated in Gamma Cell Acute Irradiation Facility at Malaysian Nuclear Agency with irradiation doses from 0.1 kGy to 2.1 kGy. The radiation sources were from two Cesium-137 sealed sources. Dose responses are crucial information for bacterial mutagenesis studies. The survival curves of viable bacterial cell count versus radiation doses were plotted to determine dose-response and lethal dose, 50% (LD50). Viable cells reduce as irradiation doses increase. The LD50 for Bacillus megaterium NMBCC50018, Bacillus subtilis NMBCC50025 and Escherichia coli were 1.2 kGy, 0.2 kGy, and 0.03 kGy, respectively. Bacillus megaterium NMBCC50018 was most resistant to gamma radiation. Dose responses between Gram-positive and Gram-negative bacteria were concluded to be different.